Biomarkers of Periodontal Tissue Remodeling during Orthodontic Tooth Movement in Mice and Men: Overview and Clinical Relevance. (23rd April 2013) - d'Apuzzo, Fabrizia; Cappabianca, Salvatore; Ciavarella, Domenico; Monsurrò, Angela; Silvestrini-Biavati, Armando; Perillo, Letizia
Abstract : Biologically active substances are expressed by cells within the periodontium in response to mechanical stimuli from orthodontic appliances. Several possible biomarkers representing biological modifications during specific phenomena as simile-inflammatory process, bone resorption and formation, periodontal ligament changes, and vascular and neural responses are proposed. Citations to potentially published trials were conducted by searching PubMed, Cochrane databases, and scientific textbooks. Additionally, hand searching and contact with experts in the area were undertaken to identify potentially relevant published and unpublished studies. Selection criteria were as follows: animal models involving only mice and rats undergoing orthodontic treatment; collection of gingival crevicular fluid (GCF) as a noninvasively procedure for humans; no other simultaneous treatment that could affect experimental orthodontic movement. The data suggest that knowledge of the remodeling process occurring in periodontal tissues during orthodontic and orthopedic therapies may be a clinical usefulness procedure leading to proper choice of mechanical stress to improve and to shorten the period of treatment, avoiding adverse consequences. The relevance for clinicians of evaluating the rate of some substances as valid biomarkers of periodontal effects during orthodontic movement, by means of two models of study, mice and men, is underlined.